Increasing accuracy and robustness of order promises. Issue 3 (1st February 2017) - Seitz, Alexander; Grunow, Martin
Abstract : Accurate order promising is a key requirement for customer satisfaction. Nevertheless, practitioners struggle with the reliability of the delivery dates they promise to customers. Consequently, the costs of demand fulfilment soar due to intensified communication, emergency processes in logistics and acquisition of costly external production resources. We identify and formalise product and process flexibilities in supply chains that can be exploited in production planning. Product flexibility is the possibility to produce several kinds of products from one predecessor product. Process flexibility is the possibility to use one production process to manufacture several products. In order to increase the accuracy and robustness of delivery dates, we develop an order promising methodology able to deal with demand mix uncertainty and heterogeneous customer order lead times. The approach anticipates changes in production plans made possible by product and process flexibilities. In a numerical study based on a case from the semiconductor industry, we demonstrate that our method increases the accuracy and robustness of order promises. For the studied case, we find that the consideration of process flexibility is more important for the generation of accurate and robust order promises than the consideration of product flexibility.